FOUR-CYCLE ENGINE - OOBA, JUNICHI; TAKII, OSAMU; NISHIMURA, HIDEHIRO (2004)
A first catalyst (9) is provided in an exhaust pipe (6), and a second catalyst (10) is provided in the exhaust pipe (6), on the downstream side of the first catalyst (9), with a spacing from the first catalyst (9). A secondary air-introducing pipe (11) for introducing secondary air is connected to a portion between the first and the second catalyst (9, 10), at a position where the difference between the maximum temperatures of the first and the second catalyst (9, 10) in a measurement operation range is within a predetermined temperature range. Un premier catalyseur (9) est placé dans un tuyau d'échappement (6) et un deuxième catalyseur (10) est placé dans ce tuyau d'échappement (6) du côté aval du premier catalyseur (9) et placé à distance de ce dernier. Un tuyau (11) d'introduction d'air secondaire est accouplé à une partie située entre le premier et le deuxième catalyseur (9, 10) dans une position où la différence entre les températures maximum du premier et du deuxième catalyseur (9, 10) se trouve à l'intérieur d'une plage de mesure déterminée.